Antoine Martel in discussions about Ukrainian literarylanguage - Radyshevskyy, Rostyslav; Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2025)
The complex issue of the formation of Slavic literary languages has fostered an intellectual dialogue among distinguished scholars, reflecting diverse concepts, methods of text analysis, historical and cultural argumentation.Antoine Martel – a polyglot, researcher of Slavic languages and culture, professor at the University of Lille – left scientific texts that profoundly influenced Slavic studies over the past century. In particular, he proposed an original conception of the emergence of the Ukrainian literary language in the second half of XVI-XVII centuries. His research examined the state and status of Ukrainian written culture and its connections with the Polish language, substantiating conclusions regarding the impact of Polish civilization on Ukrainian language consciousness during this period.At the same time, A. Martel has formulated a debatable thesis: that educated Ukrainians of the Renaissance were consciously distanced from developing and adopting a native literary language under the aesthetic and functional influence of the sophisticated models of Polish literature, especially the works of Jan Kochanowski.Martel's ideas are examined in the context of critical commentary by Yurii Sherekh, who, while acknowledging the erudition and scholarly competence of the French Slavist, presents a series of logical and analytical arguments that challenge A. Martel's position.Particular attention is given to the necessity of correlating linguistic and literary trends with the sociocultural context of the era, of regarding the linguistic influences among nations as a nonlinear process shaped by cultural dialogism, and of ensuring that analysis is grounded on representative corpus of texts.The article also discusses the criteria by which A. Martel's research works have been assessed by French Slavists, notably by the respected scholar A. Mazon.
Keywords: conceptions of literary language development; literary language; Ukrainian literary language; Slavic literary languages; Polish civilization; manuscript and written sources of the Ukrainian language; A. Martel; Y. Sherekh; A. Mazon